Trajectory of parental health-related quality of life after neonatal hospitalization – a prospective cohort study - Julia Karsch; Mascha Schönfeld; Ann-Kathrin Mühler; Susanne Tippmann; Christine Arnold; Michael S. Urschitz; Eva Mildenberger; André Kidszun (Health and Quality of Life Outcomes)
Abstract Background Health-related quality of life is an important measure of patient-reported outcomes. There is limited evidence on how parental health-related quality of life develops after neonatal hospitalization. Objective To evaluate parents’ health-related quality of life (HRQL) during the year following their infant’s treatment in the neonatal intensive care unit (NICU). Methods This prospective cohort study, conducted at a German university hospital between 2020 – 2023, examined HRQL among parents of infants hospitalized in the NICU for ≥ 14 days and parents of infants discharged from the maternity ward according to PedsQL™ Family Impact Module. Multiple linear regression analysis was performed to identify associations between cohort affiliation and differences in parental HRQL. Key secondary outcome was parenting sense of competence (PSOC). Results Participants included 131 parents of NICU infants and 122 unexposed parents. HRQL increased over time for NICU mothers (58.7 at 14 days, 70.8 at 6 months, 77.0 at 12 months after birth) and NICU fathers (69.8 at 14 days, 73.9 at 6 months, 75.7 at 12 months). NICU treatment was significantly associated with lower HRQL at 14 days (mothers: -20.26 points; P < .001; fathers: -9.40 points; P = .04), but not at 6 or 12 months after birth. At 12 months postpartum, NICU mothers showed higher PSOC compared to unexposed mothers (mean difference -4.85; P = 0.005). Conclusions Parents and especially mothers of NICU infants reported lower HRQL at 14 days postpartum. At 6 and 12 months, their HRQL improved, aligning with that of unexposed parents.